Comparative Metabarcoding and Metatranscriptomic Analysis of Microeukaryotes Within Coastal Surface Waters of West Greenland and Northwest Iceland - Elferink, Stephanie; Wohlrab, Sylke; Neuhaus, Stefan; Cembella, Allan; Harms, Lars; John, Uwe (Frontiers in Marine Science, 2020)
Climate change alters environmental conditions that are expected to have a profound effect on the biodiversity, community composition and metabolic processes of microeukaryotic plankton in Arctic and Subarctic coastal waters. The molecular biodiversity (LSU rRNA gene) of three plankton size-fractions (micro-, nano-, and picoplankton) from coastal waters of ice-influenced west Greenland was compared with fractions from ice-free northwest Iceland within their summer environmental context. Putative metabolic functions were determined by differentially expressed mRNA (metatranscriptomics) of the microplankton. Temperature and salinity variations were more closely correlated than inorganic macronutrients with metabolic functions and community composition. Temperature explained much of the community variance, approximately 20% among micro- and nanoplankton, whereas other environmental factors accounted for rather low fractional variance (<7%). Species of smaller cell-size were more evenly distributed (Pielou’s evenness index J) across regions, with a higher diversity and total abundance, and thereby indicating high plasticity. The metatranscriptomic profiles in these respective microeukaryotic communities revealed that diatoms were more plastic in their gene expression than dinoflagellates, but dinoflagellates had a more diverse, albeit homogeneously expressed, gene pool. This could be interpreted as expression of alternative lifestyle strategies, whereby the functionally more conservative diatoms fill their niches primarily through variable resource use, whereas dinoflagellates apparently differentiate their niches through more diverse lifestyles. Patterns of microeukaryotic diversity are thus primarily associated with differences in metabolic function and activity of diatom- versus dinoflagellate-dominated communities in Arctic and Subarctic waters during summer.